От берега до берега: переводы : из удмуртской лирики / Глеб Пагирев - Пагирев Глеб Валентинович (Удмуртия, 1984)
Экземпляры: с/ф № 10 (1984) / Инвентарный номер: 6326 / Сис.шифр: 84(2Рос=Удм)6 / Авт.знак: П 12 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6